Spontaneous brain activity in healthy aging: An overview through fluctuations and regional homogeneity - Montalà-Flaquer, Marc; Cañete-Massé, Cristina; Vaqué-Alcázar, Lídia; Bartrés-Faz, David; Peró-Cebollero, Maribel; Guàrdia-Olmos, Joan (Frontiers in Aging Neuroscience, 2023)
Introduction This study aims to explore whole-brain resting-state spontaneous brain activity using fractional amplitude of low-frequency fluctuation (fALFF) and regional homogeneity (ReHo) strategies to find differences among age groups within a population ranging from middle age to older adults. Methods The sample comprised 112 healthy persons (M = 68.80, SD = 7.99) aged 48–89 who were split into six age groups (< 60, 60–64, 65–69, 70–74, 75–79, and ≥ 80). Fractional amplitude of low-frequency fluctuation and ReHo analyses were performed and were compared among the six age groups, and the significant results commonly found across groups were correlated with the gray matter volume of the areas and the age variable. Results Increased activity was found using fALFF in the superior temporal gyrus and inferior frontal gyrus when comparing the first group and the fifth. Regarding ReHo analysis, Group 6 showed increased ReHo in the temporal lobe (hippocampus), right and left precuneus, right caudate, and right and left thalamus depending on the age group. Moreover, significant correlations between age and fALFF and ReHo clusters, as well as with their gray matter volume were found, meaning that the higher the age, the higher the regional synchronization, the lower the fALFF activation, and the lower gray matter of the right thalamus. Conclusion Both techniques have been shown to be valuable and usable tools for disentangling brain changes in activation in a very low interval of years in healthy aging.